Identification and preservation of External Branch of the Superior Laryngeal Nerve during thyroid surgeries at NMCTH - Joshi, Rupesh Raj; Rijal, Anupama Shah; Shrestha, Kundhan Kumar; Dhungana, Anup; Maharjan, Shova (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The most common reason for thyroid surgery is the presence of benign or malignant nodules. Subjective voice disturbance after thyroidectomy is very common, even without injury to the recurrent laryngeal nerves. One possible cause for postoperative dysphonia is injury to the External branch of superior laryngeal nerve (EBSLN). Cernea classification, which we followed in this study, is one of the most popular worldwide classifications of the EBSLN. The study was conducted with objectives to identify and classify EBSLN according to Cernia classification in Nepalese population and help surgeons understand the anatomy of the EBSLN and to preserve the nerve during thyroidectomy. Materials & Methods: A prospective observational case series of seventy-nine patients, who were diagnosed with thyroid neoplasms and underwent thyroid surgeries at the tertiary centre of Kathmandu between 1st January 2015 to 31st December 2016. All procedures were performed by transverse collar incision. We classified the anatomy of the EBSLN using Cernea classification. Results: There were total of 79 patients. Most common diagnosis and surgery were colloid goitre and hemithyroidectomies respectively. A total of 94 EBSLNs were evaluated. Cernia Type I was observed in 27.66%, type IIa in 46.80%, and type IIb in 14.89%. Incidences of types IIa and IIb, which put patients at greater risk for intra-operative injury, were observed in 61.69% in our study. The nerve could not be identified in 10.64%. Conclusion: It is possible to increase the rate of nerve identification and avoid the nerve injury even in the absence of sophisticated equipment.